Communicable disease control and health protection handbook - Hawker, Jeremy; Begg, Norman; Reintjes, Ralf.; Ekdahl, Karl.; Edeghere, Obaghe; Van Steenbergen, Jim E. (Hoboken, N.J. : Wiley-Blackwell, 2019)
'Sales handles: Clear and concise content that combines science with practical guidance. Covers basic principles of communicable disease control and health protection, major syndromes, control of individual infections, main services and activities, organizational arrangements for all EU countries and sources of further information. All chapters updated in line with recent changes in epidemiology, new guidelines for control and administrative changes. New disease chapters include Zika virus, Schistosomiasis, Coronavirus including MERS + SARS, and Ebola. Market description: Public-health physicians, epidemiologists, infection control nurses, microbiologists and those training to work in these related fields'--Provided by publisher.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed December 19, 2018)
Keywords: Communicable diseases; HEALTH & FITNESS / Diseases / General; MEDICAL / Clinical Medicine; MEDICAL / Diseases; MEDICAL / Evidence-Based Medicine; MEDICAL / Internal Medicine; Communicable diseases; Communicable Disease Control; Public health surveillance; Electronic books; Handbook; Electronic books